"Expunge Virtually All Use of the Passive Voice": How Does Style Guideline Affect Passive Voice Occurrences in Research Articles? - Humairah Fauziah; Yazid Bashtomi (National Research University Higher School of Economics, 2024)
Background: The prevalence and impact of passive voice (PV) structures in research articles have garnered attention, particularly within the context of academic publishing guidelines. Some journals' writing style guideline, for example, explicitly advises authors to eliminate passive voice instances from their manuscripts, prompting an examination of the extent to which this guideline influences authors' choices in different journal contexts. Purpose: This study aimed at comparing the frequency of passive voice (PV) structures used in research articles published by journals originating in Indonesia (henceforth, JOI) to those in research articles published by journals originating in English-speaking countries (henceforth, JOE). Method: Data were gathered from respected journals in Indonesia and the United Kingdom, both renowned for their excellence in language education and applied linguistics. After reviewing relevant literature and considering journal origins and author affiliations, we selected 34 articles (17 from each group) out of 66. We focused our analysis on the 'Introduction' and 'Method' sections, as these sections typically contain active voice in the former and passive voice in the latter. Other sections and peripheral elements were excluded. The analysis involved exporting PDFs to text files to count words and passive voice occurrences. We utilized a passive voice detector tool and manual analysis for accuracy. A t-test was conducted to compare the frequency of passive voice between the two journals. Results: The results indicated three main findings with respect to the research questions: 1) PVs in JOI occurred more frequently in the 'Method' than in the 'Introduction' section, 2) similarly, PVs in JOE occurred more frequently in the 'Method' than in the 'Introduction' section, 3) JOI comprised fewer sentences than JOE but the frequency of PVs in JOI was significantly higher than that in JOE. Conclusion: We inferred that the current guidelines seemingly affected the authors' choices of using PV. We also provided some suggestions on how to use AV and PV appropriately in the manuscript.